New records of Seira dowlingi (Wray, 1953) (Collembola, Entomobryidae, Seirinae) for New World - Nikolas G. Cipola; Nerivânia N. Godeiro; Bruno C. Bellini (Entomological Communications, 2019)
Seira dowlingi (Wray, 1953) is recorded for the first time in Peru and Brazil from five states, including Fernando de Noronha archipelago plus a new record from United States. These new records support that S. dowlingi has a wide distribution in Neotropical Region, and expanded to 34 the number of species of Seira Lubbock, 1870 found in Brazil. In addition, our revision excluded the record of Seira domestica (Nicolet, 1842) for Brazil.